Pengaruh Tekanan Blower pada Proses Pembakaran Sampah Medis Menggunakan Insinerator Statis terhadap Kualitas Abu - Pungut Pungut; Muhammad Al Kholif; Audi Arga Perwira Nagariagam Sugianto (Fakultas Teknik, 2022)
Medical waste generated from the activities of hospitals or other health facilities is very dangerous and can cause health problems for humans. One way of processing medical waste is by using an incinerator. This study aims to determine the effect of blower pressure on the medical waste incineration process on the levels of Cadmium (Cd), Chromium VI (Cr⁺⁶), and Lead (Pb) in the ash residue based on the TCLP test. The method applied is to weigh 300 kg of medical waste and then burn it in an incinerator with a blower pressure variation of 10 and 30 mbar at an optimal temperature of 1,200 °C. The results showed that the best TCLP test with a blower pressure of 10 mbar was Cd of 0.411 mg/L in experiment 2, Cr⁺⁶ of 0.143 mg/L in experiment 2, and Pb of 59.4 mg/L in experiment 3. Meanwhile, the results of the best TCLP test in Experiment 3 with a blower pressure of 30 mbar are Cd of 0.34 mg/L, Cr⁺⁶ of 0.098 mg/L, and Pb of 42.2 mg/L. The results showed that the levels of Cd and Cr+6 had met the environmental quality standards, while the Pb levels had not met the required environmental quality standards.